Characterization of Three cDNAs Obtained by Spliced Leader-PCR Screening of a Taenia solium cDNA Library - Garrido, Oswgladys (2022)
Cysticerci or metacestodes of Taenia solium cause cysticercosis, being the neurocysticercosis (NCC) the main pathology. The characterization of genes is essential for the knowledge of parasite biology, the understanding of the parasite-host relationship, and the identification of possible targets for diagnosis, treatment, and protection. The objective of this work was the molecular and bioinformatic characterization of three news cDNAs (TsTF10, TsAAP8, and TsrGAP8), obtained by spliced leader-PCR screening of a Taenia solium cDNA library. The sequences of the three cDNA were compared with the sequences in the nucleic acid and protein databases (GenBank, EMBL) and analyzed by bioinformatic programs (CDD-Search of the National Center for Biotechnology Information, Interpro of the European Bioinformatics Institute, Motif scan and Expert Protein Analysis System of the Proteomics Server from Swiss Institute of Bioinformatics). Considering the high identities with similar molecules of related helminths (Taenia asiatica, Echinococcus granulosus, Echinococcus multilocularis, and Hymenolepis diminuta) and the functional domains found, the TsTF10, TsAAP8, and TsrGAP8 genes of Taenia could act as a nuclear transcription factor gamma, a putative vacuolar ATPase membrane sector associated protein and a Rho GTPase activating protein, respectively. Although few B epitopes could be predicted in the sequences, it could be relevant to evaluate them as possible candidates for diagnosis and protection in cysticercosis. The characterization and analysis of these sequences and the prediction of their possible usefulness as antigens, vaccines, or therapeutic targets contribute to the designing and planning of future studies.